World trend in energy: An extension to DEA applied to energy and environment - Toshiyuki Sueyoshi; Mika Goto (Journal of Economic Structures, 2017)
This study proposes a use of data envelopment analysis (DEA) to assess the performance of energy industries. The DEA is a nonparametric approach that does not assume any functional form for performance assessment. The purpose of this study is to discuss how DEA can examine the current energy industries and their trends in the world. The energy is separated into primary and secondary categories. The primary energy is classified into fossil and non-fossil fuels. The fossil fuels include oil, natural gas and coal, while the non-fossil ones include nuclear and renewable energies (e.g., solar, wind, biomass, water and others). Energy consumption is essential for developing economic prosperity in all nations. However, a use of various energy resources usually produces many different types of pollutions (e.g., air, soil and water pollutions), leading to a huge damage on our society and human health. Thus, it is important for us to understand a general trend of world energy when we consider various environmental issues. This study discusses electricity as a representative of secondary energy. It is not easy to maintain a high level of social balance, so-called sustainability between economic development and environmental protection. As the initial step for sustainability development, this study summarizes a general trend of energy whose consumption has been increasing along with an economic development and a population increase in the world. Along with discussing the trend of world energy, this study describes why DEA is useful as one of the methodologies to assess a social balance between economic success and environmental protection by identifying a level of efficiency, later referred to as 'unified (operational and environmental) efficiency.' Thus, this study conveys the research necessity of DEA environmental assessment on energy and sustainability from a perspective of supply and demand on energy resources in the world.
Keywords: 330; DEA; Primary energy; Secondary energy; World energy; Environment